Analysis of Launcher’s Productivity in Erection Girder Using Time Motion Study Method - Danang Hadiyatmoko; Jati Utomo Dwi Hatmoko; M. Agung Wibowo (Civil Engineering Journal, 2023)
Erection girder is one of the determinants of the success of bridge and road work, so in its implementation, it is of concern to many parties. Apart from lifting work that uses heavy equipment with a large capacity, it is also due to the high risk of erection work. Since using heavy equipment as a tool for the erection girder, then closely related to productivity and work time. Many factors affect the productivity of heavy equipment, and one of them is time, so a well and measurable work plan is needed. This study aims to provide solutions to problems regarding the productivity of the erection girder launcher method with a time motion study analysis for each work cycle. Time Motion Study is calculated using collected data from time and productivity records. The analysis model has been carried out with the amount of data of 58 erection girder cycles with the specification of Girder Profile I with 16 meters, 30 meters, 40 meters, and 60 meters in length. The modeling results are in the form of productivity nomograms and optimal productivity of the erection girder launcher method. The optimal productivity of a 16-meter girder is 0.901 girder/hour, 30 meters girder is 0.692 girder/hour, a 40 meters girder is 0.443 girder/hour, and 60 meters girder is 0.340 girder/hour. In this study, there are some renewals from other studies. From this study, it might be known about factors that affect the productivity of erection girders, such as the distance of the girder’s stockyard, the girder’s length, and erection time. Doi: 10.28991/CEJ-2023-09-08-06 Full Text: PDF